A Case of Influenza Virus-Induced Acute Cerebellitis Treated with Steroid Pulse Therapy - Hirota, Yukiho; Minamikawa, Shogo; Ishida, Yusuke; Maruyama, Azusa; Nakagishi, Yasuo (Journal of Pediatric Neurology, 2021)
Acute cerebellitis (AC) is characterized by acute onset cerebellar ataxia brain magnetic resonance imaging (MRI) abnormalities of the cerebellum. The most common cause of AC is viral infection, and some patients with AC experience neurological sequelae. AC associated with influenza virus is extremely rare, and its prognosis and treatment are unknown. We present the case of a 2-year-old boy with influenza virus-induced AC who was treated with pulse steroid therapy. The patient presented with fever, anorexia, vomiting, malaise, altered consciousness, truncal ataxia, dysmetria, and dysarthria. He was diagnosed with influenza using a nasopharyngeal antigen test. Brain MRI showed hyperintense T2 and diffusion-weighted signal abnormalities in the cerebellar white matter and dentate nuclei bilaterally. The patient was treated with two courses of pulse methylprednisolone therapy and recovered completely in 2 months after the onset. The prognosis of AC is poorer than that of acute cerebellar ataxia, which shows similar symptoms to AC with normal brain MRI. The type of virus might also be associated with the prognosis of AC. Literature review showed that one of the five cases (including the present case, 20%) reported with influenza-associated AC was noted to have neurological sequelae, which might be more severe than those of varicella-zoster-related AC. Given that the pathogenesis of AC is assumed to be immune-mediated, pulse methylprednisolone therapy might be a good option for the treatment of influenza virus-induced AC.
Keywords: acute cerebellitis; influenza virus; steroid pulse; acute cerebellar ataxia